Analysis of Consumer Intention to Resist Eco-Label Product Purchases: an Innovation Resistance Theory Approach - Hendiawan, Adi; Wibowo , Mas Wahyu (International Journal Labs, 2025)
Eco label products have gained prominence alongside the growing awareness of environmental issues. However, consumer resistance toward purchasing eco-labeled products remains a significant barrier, especially in developing countries such as Indonesia. This study aims to analyze the influence of five innovation resistance factors on the intention to resist eco-label product purchases: usage barrier, value barrier, risk barrier, traditional barrier, and image barrier. Using a quantitative approach and PLS-SEM analysis, data were collected from 213 Millennial and Gen Z respondents across major cities in Java, Indonesia. The results indicate that value barrier, traditional barrier, and image barrier have a significant positive influence on resistance, while usage barrier shows no significant effect, and risk barrier has a negative influence. Image barrier emerged as the most dominant factor. This study contributes to the extension of Innovation Resistance Theory (IRT) in the context of environmentally friendly products and offers practical implications for industry players to build credibility and improve consumer perception of eco-labeled products